Performance of Denitrifying Microbial Fuel Cell with Biocathode over Nitrite - Zhao, Huimin; Zhao, Jianqiang; Li, Fenghai; Li, Xiaoling (Frontiers in Microbiology, 2016)
Microbial fuel cell (MFC) with nitrite as an electron acceptor in cathode provided a new technology for nitrogen removal and electricity production simultaneously. The influences of influent nitrite concentration and external resistance on the performance of denitrifying MFC were investigated. The optimal effectiveness were obtained with the maximum total nitrogen (TN) removal rate of 54.80±0.01 g m-3 d-1. It would be rather desirable for the TN removal than electricity generation at lower external resistance. Denaturing gradient gel electrophoresis suggested that Proteobacteria was the predominant phylum, accounting for 35.72%. Thiobacillus and Afipia might benefit to nitrite removal. The presence of nitrifying Devosia indicated that nitrite was oxidized to nitrate via a biochemical mechanism in the cathode. Ignavibacterium and Anaerolineaceae was found in the cathode as a heterotrophic bacterium with sodium acetate as substrate, which illustrated that sodium acetate in anode was likely permeated through proton exchange membrane to the cathode .